The Policy Delphi Method: Contribution to Policy and Strategy Within Energy Organisations: A 2013 Malaysian Case Study with Global Implications - McGeoch, M.; Brunetto, Y.; Brown, Kerry (Springer, 2014)
The policy delphi method is a process that seeks to generate the strongest possible opposing views on the potential resolutions of a major policy issue, such as strategy and policy for infrastructure and engineering asset management within asset-intensive organisations. The objectives of the policy delphi method are to: ensure that all possible options have been tabled for consideration, estimate the impact and consequences of any particular option, and to examine and estimate the acceptability of all the individual options. The committee process is commonly used to address a wide range of issues and decisions within organisations at management and operational levels. Committees dominate governance and management within nearly all types of organisations, however, it has been argued that the committee approach no longer functions as effectively in the realm of policy formulation as it once may have due to a lack of adequate structure for discussion. Due to the disadvantages of the Committee process, this research investigated the relevance and effectiveness of the policy delphi method in 2013 within the leading Malaysian energy organisation, with the provision of this practical case study of a policy delphi to elaborate the efficacy of this method for asset intensive organisations to develop strategy and policy.